Hábitos orais deletérios em escolares e sua relação com o excesso de peso e a ansiedade - Dellazzana, Amanda Alves (2014)
Objective: Evaluate the influence of the presence of deleterious oral habits on the excess body weight in scholars and its relation to anxiety. Methods: Analytical cross study developed in a Municipal Public School in the City of Santa Maria - RS, from May to June 2013. It was held anthropometry, applied a deleterious oral habits questionnaire and What I think and feel "(OQPS) - children's scale of self - application for assessment of anxiety. From the 174 students who participated in the anthropometric assessment, 110 responded to the deleterious oral habits questionnaire and 64 the scale OQPS. Data were analyzed in Stata10, it was used logistic regression with a confidence interval of 95 %, it was also calculated the median and used Wilcoxon and Kruskal - Wallis test, considering as significant p < 0.05. Results: Boys had a higher percentage of high weight (44.2 %) and higher BMI Z -score median. From the students who had at least one habit 47.9 % were overweight. All children in which the habits were present had greater risk of being overweight (p > 0.05). The presence of the habit of biting objects and mouth / tongue / cheek were the ones which showed higher scores of anxiety, with statistical difference (p < 0.05). The anxiety score was similar in relation to the nutritional status of schoolchildren. Conclusion: Overweight and presence of deleterious oral habits are prevalent in the age group between 8 and 12 years in both sexes, boys are less anxious than girls. It was not possible to observe an association between excess body weight and the presence of deleterious oral habits or even infer that anxiety is directly related to the nutritional status or the presence of deleterious oral habits.